On the problem of adjusting calculations of punitive policy of the Soviet state on labor front during the Great Patriotic War - Yu. G. Belonogov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the identification of groups of factors that artificially overstated or, on the contrary, underestimated the results of the punitive policy of the state to strengthen labor discipline during the Great Patriotic War in the industrial sector of the Soviet economy. The study is carried out on the basis of an analysis of both the changed legislative framework in the studied area and the office documentation of the Committees of the Communist Party in the Molotov region. Studying the real practice of applying laws in certain large enterprises of the Molotov region, the author concludes that there is a discrepancy between the number of actual labor crimes and the number of workers convicted of them.